Experimental and simulation study of the effect of surface functional groups decoration on CH4 and H2 storage capacity of microporous carbons - Mirzaei, Shohreh; Ahmadpour, Ali; Shahsavand, Akbar; Nakhaei Pour, Ali; LotfiKatooli, Leila; Garmroodi Asil, Ali; Pouladi, Babak; Arami-Niya, Arash (Elsevier, 2020)
© 2020 Elsevier B.V.